Medical Harm and Patient Safety- II: Medication Errors - Adhikari, N (Journal of Nepal Paediatric Society, 2011)
In this second series on Medical harm and patient safety, I will discuss Medication Errors. It is essential to review some definitions before we discuss medication errors. DOI: 10.3126/jnps.v31i1.4163 J Nep Paedtr Soc 2010;31(1):75-79